Adaptive Learning in Financial Markets - Routledge, Bryan R. (Review of Financial Studies, 1999)
We investigate adaptive or evolutionary learning in a repeated version of the Grossman and Stiglit (1980) model. We demonstrate that any process that is a monotonic selection dynamic will converge to the rational expectations asset demands if the proportion of informed traders is fixed. We also show that these learning processes have a unique asymptotically stable fixed point at the Grossman–Stiglitz (GS) equilibrium. The robustness of learning to noisy experimentation is studied using Binmore and Samuelson's (1999) deterministic drift approximation. Conditions on economic and learning process parameters for adaptive learning to lead to the GS rational expectations equilibrium are presented.